Revealing the Odonatofauna of Northeastern Brazil: new Heteragrion Selys, 1862 (Odonata: Heteragrionidae) species from Bahia state - Vilela, Diogo Silva [UNESP]; Rodrigues, Marciel Elio; Lencioni, Frederico A.A. (Magnolia Press, 2022)
Heteragrion roquei sp. nov. (Brazil, Bahia state, Municipality of Una, Fazenda Araruna, (-15.3146, -39.1621), 40 m, 19.ix.2019, M.E. Rodrigues leg., UESC) is described based on two males recently collected in Bahia state, Brazil. The new species is illustrated, diagnosed and compared with morphologically close congeners, being separated from them mainly by cercus characters, such as the medial portion and both ventrobasal/dorsobasal expansions.
Keywords: Atlantic Forest; Bahia state; Damselfly; Neotropical; new species